New occurrence of microchromosomes B in Moenkhausia sanctaefilomenae (Pisces, Characidae) from the Parana River of Brazil: analysis of the synaptonemal complex - Portela-Castro, ALD; Juilo, H. F.; Nishiyama, P. B. (Kluwer Academic Publ, 2000)
The Moenkhausia sanctaefilomenae specimens showed a karyotype consisting of 2n = 50 chromosomes with 12 metacentrics, 36 submetacentrics and two subtelocentrics. In addition to the basic karyotype, all the males specimens have cells ranging from zero to two B microchromosomes in mitotic metaphases. These chromosomes were not observed in the female specimens. C-band analysis showed a distribution pattern of characteristic heterochromatin with interstitial and centromeric blocks. However, the B chromosomes were faintly stained with C-banding and were not fluorescent with CMA(3) staining. The meiotic studies showed the formation of bivalents in metaphase I and in pachytene under an optical microscope. Through synaptonemal complex analysis with an electron microscope, the pachytene showed 25 bivalents completely paired and a small bivalent corresponding to the B chromosomes. In the same preparation, one of the B chromosomes was observed in a univalent form. on the basis of pairing behavior and morphology it is assumed that B chromosomes of M. sanctaefilomenae show homology between them and their evolutionary aspects are discussed.
Keywords: B chromosomes; Characidae; fish cytogenetics; Moenkhausia; synaptonemal complex